SNP‐based non‐invasive prenatal testing detects sex chromosome aneuploidies with high accuracy. (20th June 2013) - Samango‐Sprouse, Carole; Banjevic, Milena; Ryan, Allison; Sigurjonsson, Styrmir; Zimmermann, Bernhard; Hill, Matthew; Hall, Megan P.; Westemeyer, Margaret; Saucier, Jennifer; Demko, Zachary; Rabinowitz, Matthew; Chitty, Lyn S.; et al.
ABSTRACT Objective This study aimed to develop a single‐nucleotide polymorphism‐based and informatics‐based non‐invasive prenatal test that detects sex chromosome aneuploidies early in pregnancy. Methods Sixteen aneuploid samples, including thirteen 45, X, two 47, XXY, and one 47, XYY, along with 185 euploid controls, were analyzed. Cell‐free DNA was isolated from maternal plasma, amplified in a single multiplex polymerase chain reaction assay that targeted 19 488 polymorphic loci covering chromosomes 13, 18, 21, X, and Y, and sequenced. Sequencing results were analyzed using a Bayesian‐based maximum likelihood statistical method to determine copy number of interrogated chromosomes, calculating sample‐specific accuracies. Results Of the samples that passed a stringent quality control metric (93%), the algorithm correctly identified copy number at all five chromosomes in all but one of the 187 samples, for 934/935 correct calls as early as 9.4 weeks of gestation. We detected 45, X with 91.7% sensitivity (CI: 61.5–99.8%) and 100% specificity (CI: 97.9–100%), and 47, XXY and 47, XYY. The average calculated accuracy was 99.78%. Conclusion This method non‐invasively detected 45, X, 47, XXY, and 47, XYY fetuses from cell‐free DNA isolated from maternal plasma with high calculated accuracies and thus offers a non‐invasive method with the potential to function as a routine screen allowing for early prenatal detection of rarely diagnosed yet commonly occurring sex aneuploidies. © 2013 John Wiley & Sons, Ltd.